Research Progress on Magnetic Wheel Transmission with Magnetic Coupling Speed Regulation - Chen, Haoyang (Exploring Science Academic Conference Series, 2026)
Fluid electromechanical equipment, such as fans and water pumps, accounts for a large proportion of total energy consumption in China. Throttle speed regulation results in substantial energy loss, while variable - frequency speed regulation is prone to elect romagnetic interference and thus limited in application scenarios. A magnetic wheel transmission based on magnetic coupling transfers power via non -contact magnetic fields, featuring soft start, vibration reduction, energy savings, and overload protection. This paper summarizes the structures and speed regulation mechanisms of various magnetic couplers, including cylindrical, disc, and conical types. It systematically analyzes the performance characteristics of permanent magnet materials, magnetic conductive materials, insulating materials, and supporting structural materials for magnetic wheel transmission. It compares the loss characteristics and adaptability to working conditions of electrical steel, soft magnetic composites, and cobalt -based alloys. The significance of insulat ion coating for suppressing eddy - current losses in soft magnetic composites is clarified. Moreover, the research progress in structural optimization, electromagnetic simulation models, and eddy -current heat -dissipation design for magnetic couplers is reviewed. Engineering cases show that when this transmission device is applied to equipment in thermal power, municipal engineering, petrochemical, coal mining, and other industries, the power-saving rate ranges from 11% to 34.62%, and it can effectively reduce vibration and operational & maintenance pressure. At present, existing research still has deficiencies, such as insufficient comparison of multiple speed-regulation schemes and room for improvement in high -frequency losses and torque density. Finally, the future research directions, including high-temperature superconducting magnetic materials, novel electromagnetic calculation algorithms, and adaptive magnetic circuit regulation systems, are prospected. This study provides theoretical support for the ener gy-saving transformation of fluid load equipment and for the engineering application of magnetic transmission equipment.